2019
DOI: 10.1097/inf.0000000000002067
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Intravenous Linezolid in Premature Infants

Abstract: Intravenous linezolid was efficient and well tolerated in critically ill premature infants. PNA was the main determinant of clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 38 publications
1
38
0
2
Order By: Relevance
“…In the current study, the mean CL of linezolid in children aged 0 to 12 years was 0.13 liters/h/kg, which is consistent with the findings of a prior PK study of linezolid in pediatric patients that reported an average CL value of 0.152 liters/h/kg in 14 children aged 2 to 11 years (15). A comparison of our estimates of PK parameters with those reported in the literature is presented in Table 4 (15)(16)(17).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, the mean CL of linezolid in children aged 0 to 12 years was 0.13 liters/h/kg, which is consistent with the findings of a prior PK study of linezolid in pediatric patients that reported an average CL value of 0.152 liters/h/kg in 14 children aged 2 to 11 years (15). A comparison of our estimates of PK parameters with those reported in the literature is presented in Table 4 (15)(16)(17).…”
Section: Discussionsupporting
confidence: 89%
“…The PopPK model consists of a structural model that illustrates the concentration-time relationship and random effect models that describe the inter-and intraindividual variability of the PKs. One-and two-compartment structural models with first-order elimination were evaluated on the basis of previously reported PK models and exploratory graphical analysis (15,16). The initial structural model was selected according to visual inspection of routine diagnostic plots and various goodness-of-fit criteria, including precision and the plausibility of parameter estimation, improvement of the objective function value (OFV), the Akaike information criterion (AIC), and the Bayesian information criterion (BIC).…”
Section: Methodsmentioning
confidence: 99%
“…Una reciente publicación que incluye evaluación de neonatos prematuros, determinó que realizando los análisis FC en un modelo bi-compartamental con las dosis previamente recomendadas 75 , se lograba alcanzar el objetivo terapéutico de AUC/CIM 0-24 h en > 80 a > 90% de los casos considerando una CIM de 1 µg/mL. Si la CIM fuese de 2 µg/mL, se debería aumentar su dosificación a 12 mg/kg/dosis y administrarla cada 8 h. En este estudio se pudo comprobar que fue muy bien tolerado y no se identificaron eventos adversos de mayor magnitud 78 . Finalmente, con respecto a la seguridad de linezolid en neonatos, se han reportado aparición de neutropenia, leucopenia y trombocitopenia que están más asociadas al tiempo de tratamiento (≥ 14 días) e hiperlactacidemia intensa, y alteraciones gastrointestinales más frecuentes en edades gestacionales inferiores (< 25 semanas).…”
Section: Linezolidunclassified
“…Finalmente, con respecto a la seguridad de linezolid en neonatos, se han reportado aparición de neutropenia, leucopenia y trombocitopenia que están más asociadas al tiempo de tratamiento (≥ 14 días) e hiperlactacidemia intensa, y alteraciones gastrointestinales más frecuentes en edades gestacionales inferiores (< 25 semanas). En todos los casos, los valores regresan a la normalidad luego de suspender el fármaco [77][78][79] . También se han descrito neuropatías periféricas u ópticas en adultos y niños; generalmente ocurren después de una exposición prolongada a linezolid (≥ 28 días), aunque se reportó la producción de neuropatía óptica después de sólo 16 días de tratamiento en una mujer de 29 años 74 .…”
Section: Linezolidunclassified
“…In December 2000, linezolid was approved for use in preterm infants in the USA [8,13], but it is still off-label in few European countries [16,17]. The available supporting evidence for its use in preterm infants is based on one small open-label randomized clinical trial [18], case series [19][20][21][22][23], and case reports [13,16].…”
Section: Introductionmentioning
confidence: 99%